Legal and ethical aspects of medical standards. The practice of medical disciplinary boards - Iwona Wrześniewska-Wal (Kazimierz Wielki University, 2018)
This article takes on the issue of medical standards from the perspective of the exercise of the medical profession. In the context of evaluation of diagnosis and treatment certain problems surface in relation to the definitions of health and disease. The ambiguity of these terms is not conducive to standardization. On the other hand, there is the question whether a standard in the form of universally binding law should contain medical knowledge or merely content itself with regulating the organization of health-care. Decisions of medical disciplinary boards ("medical courts" in Polish law) can be helpful in the shaping of correct practice.